Identification of microsatellite markers (SSR) linked to a new bacterial blight resistance gene xa33(t) in rice cultivar ‘Ba7’ - Theerayut Toojinda (Maejo International Journal of Science and Technology, 2009)
This study attempts to identify a new source of bacterial blight (BB) resistance gene and microsatellite makers (SSR) linked to it. A total number of 139 F2 progenies generated from a cross between the resistant donor ‘Ba7’and ‘Pin Kaset’ were developed and used for this study. A Thai Xoo isolate, TXO16, collected from Phitsanulok province, was used to evaluate the resistance reaction in the F2 population. The segregation ratio of resistance (R) and susceptibility (S) was statistically fitted to 1R:3S model indicating single recessive gene segregation. Twenty F2 individuals consisting of 10 resistant and 10 susceptible plants were chosen for DNA analysis. Sixty-two polymorphic markers covering all rice chromosomes were used to identify the location and linked markers of the resistance gene. Four SSR markers, viz. RM30, RM7243, RM5509 and RM400, located on the long arm of rice chromosome 6, could clearly discriminate between resistant and susceptible phenotypes, and 161 BC2F2:3 individuals carrying BB resistance gene were developed through MAS using these SSR markers. This population was inoculated with TXO16 to validate and confirm the location of the gene and linked markers. The segregation ratio was statistically fitted to 1R:3S model confirming a recessive nature of the gene action in this germplasm. Phenotypic-genotypic association including five additional markers suggested that RM20590 was tightly linked to this resistance gene (R2=59.12 %). The BB phenotype was controlled by a recessive gene with incomplete dominance of susceptible allele providing intermediate resistance to Xoo pathogen in heterozygotes. The location of the gene was in the vicinity of a dominant gene, Xa7, which was previously reported. However, the resistance gene identified here was different from Xa7 because of the different nature of gene action. Consequently, this gene was tentatively designated as xa33(t). The resistance gene from rice cultivar ‘Ba7’ and the closely linked markers found in this study will be useful for rice breeders as a source to improve BB resistance through MAS in rice breeding programs.